1990
DOI: 10.1007/bf01245443
|View full text |Cite
|
Sign up to set email alerts
|

Temporal synergism of neurotransmitter affecting drugs and seasonal reproductive responses of Indian Palm Squirrel,Funambulus pennanti

Abstract: Daily injections of L-dihydroxyphenylalanine (L-DOPA, dopamine precursor) given 12 hour after 5-hydroxytryptophan (5-HTP, serotonin precursor) eliminated annual testicular regression in seasonally breeding sub-tropical Palm Squirrel that undergoes seasonal changes in responsiveness to day-length and humidity. Other temporal relations (L-DOPA given 0, 4, 8, 16 and 20 hours after 5-HTP administration) decreased/delayed the rate of regression and maintained the reproductive system at intermediate level. 12-hour-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 16 publications
1
15
0
Order By: Relevance
“…25~ long. 83~ in the month of July and acclimatized for two weeks in Laboratory condition (Chaturvedi and Jaiwal, 1990). They were fed with soaked gram seeds and water ad libitum.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…25~ long. 83~ in the month of July and acclimatized for two weeks in Laboratory condition (Chaturvedi and Jaiwal, 1990). They were fed with soaked gram seeds and water ad libitum.…”
Section: Methodsmentioning
confidence: 99%
“…Study by Chaturvedi and Jaiwal (1990) indicates that daily injections of 5-HTP and L-DOPA in several specific temporal relations, markedly influenced reproductive and hormonal conditions in Indian Palm Squirrel maintained under NDL (natural day length i.e. exposed to natural photoperiod and environmental conditions) following neurotransmitter precursor treatment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Indian Palm squirrel, Funarnbulus pennanti, L-DOPA injected 12 hr after 5-HTP (12 hr relationship) eliminated seasonal gonadal regression (Chaturvedi and Jaiwal, 1990) and squirrels were maintained continuously in breeding conditions even in non-breeding season. Second study in this series reported that L-DOPA injected 12 hr after 5-HTP may even induce redevelopment of gonad up to full breeding condition when given in sexually quiescent phase of annual cycle (Jaiwal and Chaturvedi, 1991).…”
Section: Introductionmentioning
confidence: 98%
“…A number of studies have reported that the temporal phase relation of circadian serotonergic and dopaminergic oscillations affects gonadal development in many seasonally breeding birds and mammals [1,2,3,4,5,6]. Administration of a dopamine precursor ( L -dihydroxyphenylalanine; L -DOPA) 12 h after the injection of a serotonin precursor (5-hydroxytryptophan; 5-HTP) in a 24-hour period (12-hour relation) has been reported to induce breeding conditions in these species, as well as the advancement of puberty (in the Japanese quail) [7].…”
Section: Introductionmentioning
confidence: 99%